THU0131 Very long-term functional (HAQ) status of ra. (1st June 2001) - Berthelot, JM; Laborie, Y; Glemarec, J; Prost, A; Maugars, Y
Abstract : Background: Only a few studies have attempted to determine the HAQ level of rheumatoid arthritis twenty years after onset, and how often those patients consider that RA has 'burned-out' by then. Objectives: To determine how often patients with long-lasting RA (more than 10 years'duration) consider themselves in remission and to assess their HAQ level after mean follow-up of 20 years. Methods: A questionnaire was sent to 122 patients with typical RA (100% erosive, 79% positive for rheumatoid factor) of more than 10 years'duration who had been randomly selected from the charts of 4 office-based-rheumatologists (N = 61) or a university hospital rheumatology unit (N = 61). The outcome of 33/34 patients who did not return the questionnaire was determined by phone. Results: Eighty-eight of the 122 patients (63 ± 13 years of age, RA duration 20.1 ± 8.7 years) returned the questionnaire; only 80% of whom had been seen by a rheumatologist within the last year. RA burn-out was not reported, and only 6/88 fulfilled Pinals criteria for remission. However, 26% considered themselves 'in remission' for 8.5 ± 6 months, and pain was estimated at only 4.1 ± 2.3 on a visual analogue scale 0–10. HAQ remained rather low (1.11 ± 0.84) for most patients; 46% had benefited from prosthetic surgery. Among the 34 patients who did not return the questionnaire, 7 had died (at a mean age of 74 years) and the other 27 had not seen a rheumatologist for a mean 3.9 years (even though only 41% considered themselves in remission). Conclusion: RA 'burn-out' was infrequent, even after 20 years of disease duration. Conversely, more than a fourth of patients considered themselves in remission, and disease activity was frequently low. These two factors probably explain why 40% of these patients had not seen a rheumatologist for at least a year. Although the HAQ level ranged from 0 to 2.6, it was often surprisingly low. Surgery could be largely responsible for the rather good functional outcome following diagnosis of erosive RA, even after more than 20 years' duration.